Effects of Implant-Associated Osteomyelitis on Cefuroxime Bone Pharmacokinetics: Assessment in a Porcine Model. (2nd March 2016) - Tøttrup, Mikkel; Bue, Mats; Koch, Janne; Jensen, Louise Kruse; Hanberg, Pelle; Aalbæk, Bent; Fuursted, Kurt; Jensen, Henrik Elvang; Søballe, Kjeld
Abstract : Background: The prolonged antibiotic therapy that is often needed for successful management of osteomyelitis may be related to incomplete penetration of antibiotics into the target site. The objective of this study was to assess the effects of implant-associated osteomyelitis on cefuroxime penetration into bone. Methods: Implant-associated osteomyelitis using a Staphylococcus aureus strain was induced in the right tibia in ten pigs. After five days and following administration of 1500 mg of cefuroxime, measurements of cefuroxime were obtained using microdialysis for eight hours in the implant-related bone cavity, in the adjacent infected cancellous bone and infected subcutaneous tissue, and in healthy cancellous bone and subcutaneous tissue in the contralateral leg. Measurements of the corresponding free plasma concentrations were also obtained. The extent of the infection was assessed by postmortem computed tomography (CT) scans and cultures of blood, swabs, and bone specimens. Results: Bone destruction was found in the implant cavities. No structural bone changes in the adjacent infected cancellous bone were visible on CT scans. S. aureus was grown on culture of specimens from all implant cavities and from eight of ten swabs and seven of ten bone samples from the infected bone. The areas under the concentration-time curves for the different tissues differed significantly, with the lowest area under the curve found in the implant cavity (analysis of variance; p < 0.001). Although not as notable as for the implant cavity, cefuroxime penetration into infected cancellous bone was incomplete but comparable with that in healthy bone. Despite poorer tissue penetration, slightly increased time with concentrations above the minimal inhibitory concentration (MIC) was achieved in the implant cavity up to MICs of 2 mg/L compared with the other tissues, but the time was shorter for higher MICs. Conclusions: Cefuroxime penetration into infected cancellous bone was incomplete but comparable with that in healthy bone. The destructive bone processes associated with acute osteomyelitis reduced cefuroxime penetration further. Clinical Relevance: These findings support the general clinical perception that fast diagnosis and early initiation of antibiotics before the development of implant-associated cavities is important in nonsurgical management of acute osteomyelitis.